Agent-Based Modeling and Simulation 2014
DOI: 10.1057/9781137453648_5
|View full text |Cite
|
Sign up to set email alerts
|

An agent-based simulation approach for the new product diffusion of a novel biomass fuel

Abstract: M. (2011) An agent-based simulation approach for the new product diffusion of a novel biomass fuel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…More recently, studies have highlighted the importance of the relationship between individual consumer behavior and aggregate market outcomes (Bass, 2004;Garcia, 2005;Guenther, et al, 2010;Hauser, et al, 2006). These studies have shown that individual consumer interactions, positive and negative, provide important insights about aggregate diffusion (Garber, et al, 2004;Goldenberg, et al, 2007;Goldenberg, Libai, & Muller, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, studies have highlighted the importance of the relationship between individual consumer behavior and aggregate market outcomes (Bass, 2004;Garcia, 2005;Guenther, et al, 2010;Hauser, et al, 2006). These studies have shown that individual consumer interactions, positive and negative, provide important insights about aggregate diffusion (Garber, et al, 2004;Goldenberg, et al, 2007;Goldenberg, Libai, & Muller, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Successful applications of ABMS include models to simulate the process of technological innovation (Ma & Nakamori, 2004), technological market structure evolution in electricity markets (Bunn & Oliviera, 2007), production strategies in the lumber industry (Yáñez, et al, 2009), and distribution strategies of a novel biomass-fuel (Guenther, et al, 2010).…”
Section: Abms Model Development and Computational Experimental Designmentioning
confidence: 99%
“…This search resulted in 141 publications, by taking into consideration their abstracts 89 of them found as irrelevant. [7], [8], [9], [10] Consumer Behavior 7 [11], [12], [13], [14], [15], [16], [17] Delivery 9 [15], [18], [19], [20], [21], [22], [23], [24], [25] Digital Rights Management 2 [26], [27] E-Commerce 3 [24], [27], [28] Innovation 16 [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [ [34], [58] In fact, all articles were carefully screened to meet two criteria:…”
Section: Methodsmentioning
confidence: 99%
“…We can group these papers based on the innovation types. Reference [29], [30], [31], [32], [33] is about product innovation. Reference [34] is about service innovation.…”
Section: G Innovationmentioning
confidence: 99%
“…An excellent overview on agent-based modeling for innovation diffusion and a discussion of its pros and cons in comparison with the Bass model is provided by Kiesling et al (2012); for a further review see Wakolbinger et al (2013) and for research perspectives in this field also see Peres et al (2010). An illustrative application example of an agentbased simulation of market diffusion of a novel biomass fuel is described by Günther et al (2011). Further recent applications are provided by Sonderegger-Wakolbinger and Stummer (2015) and Zsifkovits and Günther (2015).…”
Section: Market Analysismentioning
confidence: 99%